2013
DOI: 10.1159/000352089
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Activation after Experimental Cardiac Tamponade

Abstract: Background/Purpose: Cardiac tamponade is a medical emergency situation associated with a high rate of life-threatening complications, even after immediate interventions. Our aim was to characterize the acute inflammatory consequences of this event in a clinically relevant large animal model. Methods: Cardiac tamponade was induced for 60 min in anesthetized, ventilated and thoracotomized minipigs by intrapericardial fluid administration, the mean arterial pressure (MAP) being maintained in the interval of 40-45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…A sebészi beavatkozás egyszerű, könnyen reprodukálható, és jól kontrollálható. A pericardium feltöltésére krisztalloid- [23] vagy kolloidoldat [24,25], esetleg az állat saját vére [26] alkalmas. A kísérletes tamponád kialakításával egyidejűleg invazív nyomásméréssel és perctérfogat-méréssel kontrollálva validálni lehet a kardiogén sokk létrejöttét.…”
Section: Kísérletes Szerepunclassified
“…A sebészi beavatkozás egyszerű, könnyen reprodukálható, és jól kontrollálható. A pericardium feltöltésére krisztalloid- [23] vagy kolloidoldat [24,25], esetleg az állat saját vére [26] alkalmas. A kísérletes tamponád kialakításával egyidejűleg invazív nyomásméréssel és perctérfogat-méréssel kontrollálva validálni lehet a kardiogén sokk létrejöttét.…”
Section: Kísérletes Szerepunclassified
“…In an earlier study with experimental cardiac tamponade, we demonstrated activation of the complement system leading to C3 deposits in the small intestinal capillaries. 11 Accordingly, we set out to characterize the effects of the C5a inhibitor peptide acetyl-peptide-A (AcPepA) 12 on the macrocirculatory and microcirculatory changes and inflammatory reactions 24 hours after the initial insult leading to established low-flow conditions in the splanchnic area.…”
mentioning
confidence: 99%
“…In the first protocol we investigated the overall characteristics and the mesenteric consequences of temporary mechanical compression of the heart leading to microcirculatory I-R of the splanchnic system. Experimental PT is a good model to study the pathomechanism of cardiogenic shock (32,56,65,66). but it has several limitations as well.…”
Section: Study Imentioning
confidence: 99%